Violation of justice in American police department as reflected in the film Changeling - Nurullita, Dyah (Universitas Ahmad Dahlan, 2021)
This undergraduate thesis describe justice theory and propaganda theory. This is aiming at analyzing violation of justice and propaganda police towards the main character and society in American. This undergraduate thesis has two main objectives to portray the violation of justice and the police propaganda in America as reflected in the Changeling film. This research uses descriptive qualitative method. There are two types of data in this study, they are primary and secondary data. The primary data is taken from the film Changeling and secondary data are taken from books, articles, journals, and data from network sources. In this research the, writer uses an interdisciplinary study. In conducting the analysis, researchers used the theory of justice and propaganda theory. To analyze this topic, the researcher uses John Rawls's theory of justice, which is actually contradict with what happens in this film. Then the researchers used propaganda theory from Jowett and O'Donnell, which the theory shows the behavior of the police against the main characters. The result of the study shows that is Los Angeles Police Department does not serve the society wisely. They use their power to be inappropriate. It acts in a violent way, and intimidates its citizens. The evil man are protected and the good is shot dead. Justice is not always run by violating people’s right. This research also finds that people who have been given a great power, they tend to abuse the power. Moreover, in human relationship, the concept of equal treatment must be applied to avoid conflicts. People who get unfair treatment tend to fight against the bad treatment. Everyone has rights to be treated equally. Upholding justice is not always done by violation their rights. This research also finds that fairly equal treatment is valuable. People should be treated equally in any condition.